2003
DOI: 10.1172/jci14915
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of cathepsin S reduces atherosclerosis in LDL receptor–deficient mice

Abstract: Human atherosclerotic lesions overexpress the lysosomal cysteine protease cathepsin S (Cat S), one of the most potent mammalian elastases known. In contrast, atheromata have low levels of the endogenous Cat S inhibitor cystatin C compared with normal arteries, suggesting involvement of this protease in atherogenesis. The present study tested this hypothesis directly by crossing Cat S-deficient (CatS -/-) mice with LDL receptor-deficient (LDLR -/-) mice that develop atherosclerosis on a high-cholesterol diet. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
292
4
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(316 citation statements)
references
References 54 publications
16
292
4
4
Order By: Relevance
“…Mice deficient in cathepsin S in LDL receptor-null mice show decreased IEL fragmentation and reduction in atherosclerosis. 26 Cystatin C deficiency in apoE-null mice resulted in increased elastic lamina fragmentation and collagen content, which could have contributed to the dilation of thoracic and abdominal aortas. 27 It remains controversial whether cystatin C deficiency affects atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in cathepsin S in LDL receptor-null mice show decreased IEL fragmentation and reduction in atherosclerosis. 26 Cystatin C deficiency in apoE-null mice resulted in increased elastic lamina fragmentation and collagen content, which could have contributed to the dilation of thoracic and abdominal aortas. 27 It remains controversial whether cystatin C deficiency affects atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…systems might also contribute to atherogenesis 6,24 and vascular remodeling. [12][13][14][15] We believe that our experiments represent the first characterization of the expression of elastolytic cathepsins and their inhibitor in the rat carotid artery balloon-injury model.…”
Section: Discussionmentioning
confidence: 99%
“…6,22,23 More interestingly, it has recently been reported that deficiency of cathepsin S reduced athrosclerosis in low-density lipoprotein receptor-deficient mice. 24 However, the expression of these cathepsins during neointima formation remains unknown. The expression and activity of cathepsins are tightly controlled at several levels.…”
mentioning
confidence: 99%
“…Although most are rapidly inactivated at the neutral pH found in the extracellular space, cathepsin S maintains 64% of its peak activity at pH 7.5 [20]. Cathepsin S RNA is increased in atherosclerotic lesions in mice [21] and its deficiency reduced elastin fiber fragmentation in hypercholesterolemic mice [22]. Cystatin C is a cathepsin inhibitor, and its mRNA is reduced in human aortic aneurisms, and its deficiency increases elastin fragmentation in hypercholesterolemic mice [11].…”
Section: Introductionmentioning
confidence: 99%